A novel characterization of alginate-attapulgite-calcium carbonate (AAC) gel adsorption in bacterial biodegradation of used engine oil (UEO) - Elhamrouni, Izeddin Abdalla; Ishak, Mohd Yusoff; Wan Johari, Wan Lutfi; Halimoon, Normala (Taylor & Francis, 2023)
Biodegradation of used engine oil (UEO) that pollutes the environment is attracting increasing attention. The aim of this study was to characterize the adsorption of used engine oil (UEO) and the immobilization of UEO biodegraders in Ochrobacterium intermedium LMG 3301 and Ochrobacterium intermedium LMG 3301 plus Bacillus paramycoides MCCC1A04098 (BC) using alginate-attapulgite-calcium carbonate (AAC). Twenty AAC beads were tested separately in 20 mL of soil water extract (SWE) and hexane containing 1% UEO for their adsorptive capacities of UEO in 50-mL capped flasks. The results showed that the UEO removal efficiency (%RE) was bead-number dependent, recording a maximum of 83 ± 0.32% in SWE, and 11.50 ± 0.52% in hexane correlating with the highest number of AAC-granules (20 beads). The 1st order kinetics in SWE showed a UEO adsorption rate, K1 (h−1), of 0.11–0.15 h−1 correlating with 20 AAC-granules and 1, 2, 3 and 4% (w/v) UEO. The intra-particle diffusion kinetic model suggested that intra-diffusion was the main mode of mass transfer in AAC granules. The microscopic study and 2,3,5-triphenyltetrazolium chloride (TTC) positive stain showed that bacteria grew well in AAC. This result demonstrates that this matrix can be applied in the formulation of novel adsorptive granular formulas for bioremediation of UEO.